Use Of Organic Fertilizer and IPM in Certified Organic Rice Farming in East Java - Winarno, Dinariningrum Rahma; Tarno, Hagus; Mudjiono, Gatot (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2024)
This study aims to analyze the effect of organic fertilizer use and Integrated Pest Management (IPM) on the success of certified organic rice farming in East Java. The research method used is descriptive quantitative with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. Data was collected by surveying 100 organic rice farmers in Kediri District. The results showed that the use of organic fertilizers and IPM significantly increased the productivity of organic rice. Organic fertilizers, such as compost and animal manure, can improve soil fertility and crop yields. Meanwhile, IPM helps control pests without using chemical pesticides. The SEM-PLS model confirmed that both variables positively and significantly influence the success of organic rice farming. The results also show that farmers who implement organic farming have a higher level of environmental awareness and are more concerned about consumer health. However, some challenges are still faced, such as limited market access and farmers' lack of knowledge about organic farming techniques. Therefore, more intensive efforts are needed to provide education and training to farmers, as well as to develop policies that support the development of organic farming. In conclusion, the application of organic fertilizer and IPM is the key to the success of organic rice farming in East Java. With the right support, organic farming can be a sustainable solution to increase productivity, preserve the environment, and improve farmers' welfare.